SCHOOL CULTURAL CONVENTION AND A PURPOSE IN THE DEVELOPMENT OF THE CHARACTER OF STUDENTS IN ELEMENTARY SCHOOL - Rahmad Khodari; Salsabila Anindiyah (Cirebon International Conference on Education and Economics Proceeding, 2024)
The main problem of this research is the cultivation of school culture, student personality and character. The purpose of this research is to study the role of cultural achievement in shaping students' personality traits. The subjects of this research were school principals, teachers, students and parents. Data collection techniques use observation, interviews and recording. Data analysis in research uses data collection, data reduction, data presentation and drawing conclusions. The research results show that Cirebon Elementary School implements school culture well. The school culture formulated and implemented by the school is the 3S culture (Smile, Greet, Greet, Polite) and 5K culture (Cleanliness, Security, Order, Beauty and Home). By forming a school culture that runs optimally, it can foster the character of discipline, creative character, character of love for the environment, character of social care, character of honesty, character of using time, character of tolerance, character of mutual respect, character of compassion and character of responsibility. These positive qualities must always be cultivated and continuously practiced so that all school staff have noble personalities.